Indigenous technique of fabricating vaginal mould for vaginal reconstruction and uterine drainage in McIndoe vaginoplasty using 10 ml syringe - Brijesh Mishra; Gaurav Janavar; Yashodhara Pradeep; Arun K. Singh; Vijay Kumar; Divya N. Upadhyay (Indian Journal of Plastic Surgery)
Absence of vagina poses multitude of physical and psychosocial problems in woman's life. 10% of Mayer- Rokitansky-üster-Hauser (MRKH) syndrome patients with high vaginal septum and vaginal atreisa has additional issue of draining uterine cavity. MC Indoe vaginoplasty is universally acceptable and widely practiced procedure for neocolposis reconstruction. Simultaneous reconstruction of vagina with simultaneous continued uterine drainage presents surgical challenge. We offer a simple solution of creating a vaginal mould using a 10 ml disposable syringe, which enables graft application of neovaginal cavity with simultaneous protected uterine drainage per vaginum. Total 10 patients were included in this study of which 4 needed uterine drainage procedure in addition to neovaginal creation. All the patients fared well, there were no problems regarding graft loss or vaginal mould extrusion etc. Fabrication of mould for graft enables easy dressing changes with out disturbing the skin graft. This innovation offers a simple easily reproducible and cheap way of fabricating vaginal mould for McIndoe vaginoplasty. It is especially useful for neovaginal graft application and simultaneous uterine drainage.